Diagnostic Accuracy of Different Methods in Detecting Factor V Leiden Mutation in Tertiary Care Centre - Barlas, Sidra; Robert, Helen Mary; Mahmood, Asad; Mahmood, Rafia; Khurshid, Ayesha; Khan, Saleem Ahmed (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the diagnostic accuracy of clotting based APCR assay in determining Factor V Leiden mutation with PCR as gold standard and to establish the frequency of factor V Leiden mutation in patients presenting with thrombophilia as well as to study their clinical presentations and association with arterial or venous thrombosis.Study Design: Cross sectional study.Place and Duration of Study: Army Forces Institute of Pathology (AFIP), Rawalpindi Pakistan, from Dec 2018 to Sep 2019.Methodology: A total of 230 patients were recruited which presented with DVT and other thrombotic conditions. Acquired causes of Factor V Leiden mutation were excluded from our study. For Screening tests APCR, blood was collected in 3.2% sodium citrate tubes while for PCR blood was collected in K2 EDTA tubes.Results: On Screening, APCR test 44 (19.29%) showed positive results with cut-off value of